SEED MEDIATED SYNTHESIS OF HEXAGONAL S-DOPED ZnO NANOROD AND ITS PHYSICAL PROPERTIES - Yolanda Rati; Akrajas Ali Umar; Yanuar Hamzah; Ari Sulistyo Rini (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
Sulfur-doped zinc oxide (S-ZnO) nanorod has been successfully synthesized via the seed-mediated hydrothermal method with different sulfur concentrations (0%, 1%, 2.5%). This research aims to study the influence of the concentration of sulfur on the structure, morphology, and optical properties of ZnO as a promising material in a wide range of applications. Crystal structure, morphology, and optical properties of the samples were characterized using X-Ray Diffraction (XRD), Field Emission Electron Scanning Microscopy (FESEM), and UV-Vis Spectroscopy, respectively. The XRD pattern shows the strongest peak at 2θ = 34.43° for crystal orientation of (002). The crystallinity properties of the S-ZnO sample are higher compared to the ZnO sample. The FESEM images of the 1% S-ZnO sample exhibit the highest nanorod density arrangement. The optical absorbance of the higher sulfur dopant possesses a higher optical absorption peak on the UV-Vis spectrum. The results indicate that S doping to ZnO can alter the structural, morphological, and optical properties of ZnO.